Takayasu Arteritis Presenting with Bilateral Common Carotid Artery Involvement in a Young Patient:A Case Report - Akter, Sharmin; Bari, Md Shafiqul (Journal of Medicine, 2026)
Takayasu’s arteritis is a rare, chronic form of large- and medium-vessel vasculitis, predominantly affecting the aorta and its primary branches. Histopathologically, it is characterized by mononuclear cell infiltration and granulomatous inflammation of the vascular media, resulting in progressive arterial wall thickening, stenosis, occlusion, or aneurysmal dilation. Involvement of the common carotid arteries is a notable but atypical manifestation, often contributing to diagnostic complexity. The disease can lead to serious complications, including stroke, ischemic heart disease, pulmonary hypertension, secondary systemic hypertension, and aneurysm formation. Diagnosis is primarily based on a combination of clinical presentation and angiographic findings. J MEDICINE 2026; 27(1): 55-57